If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(-2/3)*y = 16 // - 16
(-2/3)*y-16 = 0
-2/3*y-16 = 0 // + 16
-2/3*y = 16 // : -2/3
y = 16/(-2/3)
y = -24
y = -24
| (9x+2)(x^2+6x)= | | a+7(3a+-2)=96 | | .06a=-2.52 | | (4(8x-2))/3x | | 5/9+a=-4/9 | | x-(-5)=230 | | (-21-9b)+15= | | 60x[10s]= | | Y=80+0.6Y+30 | | 4(7x+6)=-60 | | 9v^2-10v+1= | | 24=12/x | | N+32=636 | | a+7(3a+-2)=86 | | 6x^2-35x+49= | | df+10h=3ford | | a+7(3a+-2)=100 | | 4=p/4 | | 1.5a+8-0.4a=-7 | | a+7(3a-2)=13 | | 0.3t=1.5fort | | 2x=8/3 | | 5N=-1120 | | 4=8/3/2/3 | | a+5(2a+8)=84 | | y/15+4=21 | | 1fourthk-1=7 | | 18=6/1/3 | | a+5(2a+8)=42 | | 6(4-2x)=132 | | -4/5w+1/4+1/5+1/3w | | 6-2m=m-3 |